The facile construction of the phthalazin-1(2H)-one scaffold via copper-mediated C–H(sp2)/C–H(sp) coupling under mild conditions - Wei Zhu; Bao Wang; Shengbin Zhou; Hong Liu (Beilstein Journal of Organic Chemistry, 2015)
A novel strategy for the construction of the phthalazin-1(2H)-one scaffold has been developed by means of a copper-mediated cascade C–H/C–H coupling and intramolecular annulations and a subsequent facile hydrazinolysis. This C–H activation transformation proceeds smoothly with wide generality, good functional tolerance and high stereo- and regioselectivity under mild conditions. Through the removal of the directing group, the resulting moiety could easily be transformed into the phthalazin-1(2H)-one scaffold, which is known to be a privileged moiety and a bioactive nucleus in pharmaceuticals.